Gut microbiota composition and variation in Baduy infants living traditional lifestyles in Banten, Indonesia - DERICO HITIPEUW; RAISHA NURANINDITA; BAGOES WIDJANARKO; FAUZI MUH (Society for Indonesian Biodiversity, 2025)
Abstract. Hitipeuw D, Nuranindita R, Widjanarko B, Muh F. 2025. Gut microbiota composition and variation in Baduy infants living traditional lifestyles in Banten, Indonesia. Biodiversitas 26: 4522-4533. Early-life gut microbiota development shapes immediate and long-term health. Studying infants in traditional, pre-industrial populations provides insights into natural microbial colonization, yet data on microbiota assembly in minimally medically exposed indigenous communities remain scarce. This study aimed to characterize the gut microbiota profiles of infants from the Baduy community of Indonesia, an indigenous population that maintains traditional practices with minimal exposure to industrialization. Fecal samples were collected from two Baduy infants aged 12-13 months (one male and one female) living under traditional conditions. Total genomic DNA was extracted using standardized protocols, and full-length 16S rRNA gene sequencing (V1-V9 regions, 1484 bp) was performed using Oxford Nanopore technology to achieve species-level taxonomic resolution. Alpha diversity metrics, including the Shannon diversity index, Simpson index, and species richness estimators (Chao1 and ACE), were calculated to assess within-sample microbial diversity. Female infants (13BL_P) exhibited higher Shannon diversity (3.44 vs 3.03) and were dominated by beneficial taxa, including Faecalibacterium (Firmicutes), Bifidobacterium (Actinobacteria), and Anaerobutyricum (Firmicutes). Conversely, the male infant (12BL_L) demonstrated higher species richness (543 vs. 511 observed species) but was dominated by potentially pathogenic genera, including Enterococcus and Streptococcus (both Firmicutes), alongside Bifidobacterium. Preliminary findings indicate significant microbiota variability within culturally similar traditional populations, suggesting that host factors affect microbial colonization. This study provides baseline microbiota data for the Baduy population and offers frameworks for investigating gut diversity in indigenous communities.